2022
DOI: 10.1186/s12891-022-05494-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly destructive osteonecrosis of the humeral head after arthroscopic rotator cuff repair: a case report

Abstract: Background Cases of rapidly destructive osteonecrosis (RDON) of the humeral head after arthroscopic rotator cuff repair (RCR) have rarely been reported, which has prevented a clear consensus on the cause of osteonecrosis. Case presentation A 63-year-old woman without a history of trauma underwent arthroscopic RCR after being diagnosed with a medium-sized full-thickness rotator cuff tear for symptoms of left shoulder pain for six months. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Arthroscopic rotator cuff repair using suture anchors may result in HH AVN. Multiple case reports have suggested that suture anchors may result in subsequent AVN development due to postsurgical interruption of blood supply 25,26,27 . However, others have suggested that the exact relationship between rotator cuff anchors and HH AVN development is unclear, but surgeons should be aware of this potential complication 28 .…”
Section: Etiology Of Humeral Head Avnmentioning
confidence: 99%
“…Arthroscopic rotator cuff repair using suture anchors may result in HH AVN. Multiple case reports have suggested that suture anchors may result in subsequent AVN development due to postsurgical interruption of blood supply 25,26,27 . However, others have suggested that the exact relationship between rotator cuff anchors and HH AVN development is unclear, but surgeons should be aware of this potential complication 28 .…”
Section: Etiology Of Humeral Head Avnmentioning
confidence: 99%